Integration of Advanced Metering Infrastructure for Mini-Grid Solar PV Systems in Off-Grid Rural Communities (SoAMIRural) - Duah, Daniel Y.A.; Marful, Alexander Boakye (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Solar energy is considered a promising source of power generation in sub-Saharan Africa due to the high sunshine in these areas. Deploying decentralised solar-powered mini-grid systems to provide access to electricity in rural areas is fraught with difficulties in accurately predicting consumption, automatic monitoring, and operation sustainability to support the socio-economic conditions of rural communities. This study proposed SoAMIRural, which integrates solar PV minigrid and advanced metering infrastructure for rural communities. SoAMIRural was implemented and tested for a case study community in Ghana. Solar PV Selection Equation Matrix (SPSEM) and Sample Size Equation (SSE) were used to determine the sustainable demand generation capacity of 24 kVA. Load estimations and need assessments were conducted to ascertain the rural community’s electric load and priority needs. SoAMIRural was evaluated with an error margin of 5%, resulting in 95% accuracy in energy consumption threshold management and monitoring to ensure energy conservation and sustainability of the mini-grid system. This study maps out a conceptual framework for a smart solar PV mini-grid system for rural communities and its advantages in realising SDG 7 in Ghana by 2030.